2017
DOI: 10.17478/jegys.2017.65
|View full text |Cite
|
Sign up to set email alerts
|

Preservice Preschool Teachers Views on the Characteristics of Gifted Children

Abstract: This study aims to investigate preservice preschool teachers' views on gifted children. Mixed method was conducted in the study. "The Scale for Rating the Behavioral Characteristics of Gifted and Talented Students", developed by Şahin (2012), and semi-structured interview forms were used. The findings indicate that preservice preschool teachers associate giftedness with cognitive characteristics in general. Therefore, they usually focus on cognitive skills when the basic characteristics of gifted children are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…Teachers likewise noted that some of their students were reportedly advanced in some areas of physical development. Some gifted children's physical or psychomotor skills developed faster than most children their age (Yazici et al, 2017). For instance, parents in Ogurlu and Çetinkaya (2012) study, reported that their gifted children walked earlier or toilettrained faster.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Teachers likewise noted that some of their students were reportedly advanced in some areas of physical development. Some gifted children's physical or psychomotor skills developed faster than most children their age (Yazici et al, 2017). For instance, parents in Ogurlu and Çetinkaya (2012) study, reported that their gifted children walked earlier or toilettrained faster.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies showed that teachers often associate giftedness with more positive characteristics (Moon and Brighton, 2008), and defined it based on gifted students' exemplary skills and abilities, such as cognitive capacities, motor skills, and social skills (Yazici et al, 2017). Overall, teachers often explained that the skills that these children possess are significantly more developed compared to children's chronological age.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Teachers are the key to changing and improving the quality of Education (Prachagool, Nuangchalerm, Ganakumaran, & Dostal, 2016). They have a big duty to recognize, identify, and know the characteristics of their students so that positive interactions are created in providing advanced education to young people (Kaendler, Wiedmann, Rummel, & Spada, 2015;Yazici, Akman, Uzun, & Kardes, 2017;Macaulay, Betts, Stiller, & Kellezi, 2018). Preservice teachers must have a good understanding of helping students develop thinking skills (Amponsah, Kwei, & Ernest, 2019) by paying attention to individual needs and abilities (Agbowuro, Saidu, & Jimwan, 2017).…”
Section: Introductionmentioning
confidence: 99%